Complexity theory, the capability approach, and the sustainability of development initiatives in education. Issue 5 (3rd September 2019) - Szekely, Emilia; Mason, Mark
Abstract: We defend in this paper the importance of redistributing power in the field of education development by enhancing the self-sustainability of education initiatives and minimizing their roots in dependency – these as pre-requisites for improving their sustainable development outcomes. We do this by considering an education development initiative run by the Barefoot College in India, and then developing an explanatory model based in complexity theory (as expounded by Edgar Morin) and in the capability approach (as developed principally by Amartya Sen and Martha Nussbaum). We conclude that such a redistribution of power would help to ensure that education is better connected to its development context, more relevant to the interests and needs of the community it serves, and its quality enhanced. More generally, we reinforce existing arguments – but from the perspective and imperative of sustainability – why it is in the interests of policy-makers to devolve power and to provide resources to such initiatives. Doing so would enhance governments' prospects of realizing their education and social development goals. The arrogation of power and resources towards the centre, an almost natural impulse in policy-making, is, in the end, counter-productive, and threatens sustainable education and social development.